THE INFLUENCE OF FACILITIES ON THE MOTIVATION OF TOURISTS VISITING THE JAM GADANG BUKIT TINGGI, WEST SUMATRA - Anis Darsiah; Vienna Artina Sembiring; M. Rafi Salim; Dian Octarina (Universitas Islam Lamongan, 2024)
Bukittinggi City is a city in West Sumatra province with the second largest economy after Padang City. As a tourism city, the City of Bukittinggi is starting to develop itself by building tourist facilities to support its tourist attractions. This research aims to determine the motivation of tourists who visit the Jam Gadang Tourism Area, Bukittinggi City, tourists' considerations in choosing tourist facilities when visiting the Jam Gadang Tourism Area, and the influence of tourist facilities on tourist motivation to visit the Jam Gadang Tourism Area. The research method used was descriptive, the research object was 120 respondents visiting the Jam Gadang Tourist Area. The results of this research are the need to provide expansion of the parking area as an additional facility in the Jam Gadang Tourist Area and the need to provide a place for souvenir sellers in the Jam Gadang Tourist Area so that gadang traders gather in one place that has been provided to sell so that it becomes orderly and organized.